The effect of transformational leadership and organizational culture on employee performance - Clara Vidhia (Institute of Computer Science (IOCS), 2023)
Organizational leadership and culture are factors that shape and help others to achieve planned goals in relation to organizational success. This study aims to determine the effect of Transformational Leadership and Organizational Culture on Employee Performance. This type of research is quantitative with a total of 100 respondents. The results of the study show that the value of Sig. = 0.000 < α = 0.05, and calculated F value = 439.36 > F table = 3.09. Thus, Transformational Leadership and Organizational Culture have a significant effect on Employee Performance variables. The results of this study are expected to have an impact as material for consideration in making policies related to applied leadership and organizational culture in order to increase employee professionalism.